A Weather Model for Simulating Offshore Construction Alternatives - Rothkopf, M. H.; McCarron, J. K.; Fromovitz, S. (Management Science, 1974)
The time and cost required for offshore construction operations are often dominated by the influence of weather, particularly wave heights. Historical wave height data can be summarized in a simple probabilistic model that can be used in a Monte Carlo simulation of the construction operations. Such a simulation has been used effectively to evaluate alternative bids on pipeline projects in the Gulf of Mexico. This paper describes the Markovian wave height model we have incorporated in the simulation.